2018
DOI: 10.1038/s41426-018-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of highly pathogenic avian influenza A(H5N1) viruses in Indonesia following the reassortment and acquisition of genes from low pathogenicity avian influenza A virus progenitors

Abstract: The highly pathogenic avian influenza (HPAI) A(H5N1) virus is endemic in Indonesian poultry and has caused sporadic human infection in Indonesia since 2005. Surveillance of H5N1 viruses in live bird markets (LBMs) during 2012 and 2013 was carried out to provide epidemiologic and virologic information regarding viral circulation and the risk of human exposure. Real-time RT-PCR of avian cloacal swabs and environmental samples revealed influenza A-positive specimens, which were then subjected to virus isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
1
14
0
2
Order By: Relevance
“…A parallel study on contacts of different poultry sectors revealed that backyard chicken farms have the highest contact rate ( 30 ), which may have facilitated reassortment in West Java. Of interest, a recent study described reassortant HPAI H5N1 viruses in samples collected from live-bird markets associated with suspected human HPAI H5N1 cases in Indonesia ( 13 ). More intense surveillance programs are required to confirm the prevalence and distribution of the clade 2.1.3.2a and 2.3.2.1c subgroups and its reassortments and to be able to unveil the transmission of HPAI from different sectors, vaccination practices, and regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A parallel study on contacts of different poultry sectors revealed that backyard chicken farms have the highest contact rate ( 30 ), which may have facilitated reassortment in West Java. Of interest, a recent study described reassortant HPAI H5N1 viruses in samples collected from live-bird markets associated with suspected human HPAI H5N1 cases in Indonesia ( 13 ). More intense surveillance programs are required to confirm the prevalence and distribution of the clade 2.1.3.2a and 2.3.2.1c subgroups and its reassortments and to be able to unveil the transmission of HPAI from different sectors, vaccination practices, and regions.…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the epidemiology of HPAI H5N1 requires more intense monitoring of outbreaks of HPAI in Indonesia and performing genetic and phylogenetic analysis on viruses detected during these outbreaks. However, recent information on the genetic divergence of HA, and in particular on other gene segments, is very limited ( 8 , 11 – 13 ), and samples are often collected in a nonsystematic way. Therefore, the aim of this study was to perform genetic and phylogenetic analysis on recent HPAI H5N1 viruses that were obtained from poultry during active searches for outbreaks in West Java, a province of Indonesia.…”
mentioning
confidence: 99%
“…Three reassortant viruses (A/Muscovy Duck/East Java/ SB29/2012, A/Muscovy Duck/East Java/LM47/ 2012 and A/Ck/East Java/BP21/2012) possessed PB2, PB1 and NS genes of LPAI virus, while the surface glycoproteins (HA and NA) and other internal genes (PA, NP and M) were contribution of HPAI A(H5N1) virus lineage. The experimental data of the reassortant HPAI A(H5N1) viruses showed slight attenuation possibly due to acquisition of LPAI internal genes to HPAI virus [8]. In 2017, the government of Indonesia has officially announced the introduction of enzootic H9N2 subtype; however, it is still poorly documented.…”
Section: Indonesia Situationmentioning
confidence: 99%
“…The number of human deaths in Indonesia were outgrowing to 150 by 2011 ( Figure 1) [2,[5][6][7] with 46% reported to have direct contact with infected poultry [7]. Although, to date the virus demonstrated inefficient person-to-person transmission, ongoing outbreaks in poultry pose warning to possibly establish human reassortant Avian Influenza virus [8]. New outbreaks of H5N1 in 2014 in Cambodia, China, India, Korea, Lybia, Russia and Vietnam have shown high adaptability in a heterogeneous ecosystem, requiring urgent need for reliable surveillance tool to improved strategies to control and eradicate this enzootic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the HPAI-H5N1 clade 2.3.2.1 affected duck farms in Central Java, Yogyakarta and East Java. Then, the virus became the predominant clade circulating in Indonesia (Dharmayanti et al, 2014(Dharmayanti et al, , 2018Wibawa et al, 2018).…”
mentioning
confidence: 99%